2016
DOI: 10.1371/journal.pone.0157339
|View full text |Cite
|
Sign up to set email alerts
|

PEP and TasP Awareness among Italian MSM, PLWHA, and High-Risk Heterosexuals and Demographic, Behavioral, and Social Correlates

Abstract: Post-exposure prophylaxis (PEP) has been proposed as a strategy to prevent the acquisition of HIV infection after certain high-risk exposures, and treatment as prevention (TasP) is also being advocated as a means to reduce sexual transmission of HIV. The aim of this study was to investigate the prevalence of PEP and TasP awareness and their demographic, behavioral, and social correlates in Italy. We conducted a cross-sectional survey of 1,028 high-risk heterosexual men and women, 1,874 non-HIV positive MSM (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 48 publications
5
33
0
4
Order By: Relevance
“…In samples of HIV-negative MSM in the United States, awareness of PEP has ranged from 41.0% (Dolezal et al, 2015) to 47.0% (Liu et al, 2008). This level of awareness is also higher than those observed in samples of MSM in Australia (Zablotska et al, 2011), Canada (Lin et al, 2016), Italy (Prati et al, 2016), and Spain (Fernández-Balbuena et al, 2013). However, the association between the disclosure of one’s sexual orientation to physician and awareness of PEP is supported by previous literature (Mehta et al, 2011).…”
Section: Discussionmentioning
confidence: 57%
“…In samples of HIV-negative MSM in the United States, awareness of PEP has ranged from 41.0% (Dolezal et al, 2015) to 47.0% (Liu et al, 2008). This level of awareness is also higher than those observed in samples of MSM in Australia (Zablotska et al, 2011), Canada (Lin et al, 2016), Italy (Prati et al, 2016), and Spain (Fernández-Balbuena et al, 2013). However, the association between the disclosure of one’s sexual orientation to physician and awareness of PEP is supported by previous literature (Mehta et al, 2011).…”
Section: Discussionmentioning
confidence: 57%
“…Alternatively, an unmeasured confounding variable such as HIV treatment optimism or prevention fatigue may be contributing to both lower levels of perceived risk and to higher perceived accuracy of the message 36. In addition to these factors, having engaged in recent serodiscordant CAS was a strong and independent predictor of higher perceived accuracy, as has been identified in prior research on beliefs about TasP 28, 29. Similar to HIV risk perception, individuals who better understand TasP and other aspects of HIV prevention may more accurately perceive and feel in control of their own HIV transmission risk, thus leading to what may appear to be greater risk compensation (though behaviours could objectively be lower risk and this could simply be masked by insufficient detail in the collection of these aggregated sexual behaviour data).…”
Section: Discussionmentioning
confidence: 67%
“…Terrence Higgins Trust issued a press release citing data from a 2017 YouGov survey of 2022 British adults in which they found that only 9% were aware that individuals with an undetectable viral load cannot transmit the virus to partners 27. In addition to differences between HIV‐positive and HIV‐negative individuals, research has demonstrated that engaging in condomless sex is associated with stronger beliefs in TasP 28, 29.…”
Section: Introductionmentioning
confidence: 99%
“…Explicações para a diferença no acesso à informação se devem, em parte, ao fato de os HSH manterem mais relacionamentos a partir de sites de encontro na internet, onde campanhas informativas são frequentemente vinculadas e pela maior presença em redes de apoio, como ONGs e coletivos, na qual informações sobre métodos e estratégias de prevenção costumam circular com mais receptividade. A proximidade com o estigma da aids entre HSH, devido à intensa associação nos primeiros anos da epidemia, também se mostrou associada ao maior conhecimento sobre PEPsexual (FERNÁNDEZ-BALBUENA et al, 2014;MEHTA et al, 2011;PRATI et al, 2016;WALTERS et al, 2017).…”
Section: Homem Que é Homem Também Tem Hiv?unclassified
“…Homens heterossexuais negros e pobres, por exemplo, são ainda mais invisibilizados nas estratégias e programas de prevenção à infecção pelo HIV em comparação aos HSH ou homens brancos em geral (ADIMORA et al, 2006;BOWLEG et al, 2014;BOWLEG;RAJ, 2012;CROSBY et al, 2013;BOWLEG, 2012); (CHAN et al, 2013;LUQUE et al, 2007;MAYER et al, 2012;RABAUD et al, 2005;TISSOT et al, 2010). (HEUKER et al, 2012;KÖRNER;HENDRY;KIPPAX, 2006;MARTIN et al, 2004;POYNTEN et al, 2009;PRATI et al, 2016). BECK, 2011; PERRUSI; FRANCH, 2012).…”
Section: Homem Que é Homem Também Tem Hiv?unclassified